ANALISIS KEPRIBADIAN TOKOH KAI AMAK DALAM NOVEL GALUH HATI KARYA RANDU ALAMSYAH - Sumiharti Sumiharti; Ronizar Ilham (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
This research is aimed at describing the character of Kai Amak in the novel Galuh Hati by Randu Alamsyah. This research uses qualitative descriptive method. The primary data is in the form of sentences and expressions which represents id, ego, and super ego occured in the novel Galuh Hati by Randu Alamsyah. In collecting the data, the documentation technique is used. Based on the result of the analysis, it is found that there are 45 expressions which represents id, ego, and super ego. There is 16 expressions of id aspect which can be found in his lust towards eat and drink, sex, ignoring the pain or uncomfortable feeling. There is 20 expressions of ego aspect which can be seen from his logic, problem-solving, and decision-making. Moreover, there is 9 expressions of super ego aspect which can be seen from his feeling of shame, guilty, and regret. So, it can be concluded that the character of Kai Amak has the id, ego, and super ego personality.